Study of Influential Factors of the Vibration Modal of the Rocket Equipment Bay and Structural Improvement Based on Finite Element Analysis - Chenghu Li; Guanlin Han; Chunxu Duan (International Journal of Aerospace Engineering)
In this paper, the study focuses on influential factors of the vibration modal of the equipment bay of a carrier rocket and the structural improvement of the equipment bay by using finite element modal analysis. The finite element analysis focuses on the influences of the mass of the inertial bracket, the thickness of parts of the inertial bracket, and the stringer thickness on the first modal frequency of the equipment bay. As the analytical results show, the vibration displacement of mounting panels can be greatly reduced when the equipment bay is added with mass, and the vibration of the equipment bay with mass mainly occurs on the inertial bracket (without mass, the maximum vibration displacement occurs on the mounting panel); the top surface thickness of the inertial bracket has the maximum influence on the first modal frequency of the equipment bay, the stringer thickness and the side thickness of the inertial bracket have relatively high influence on the first modal frequency, the rib thickness of the inertial bracket has relatively low influence on the first modal frequency, and the beam thickness of the inertial bracket has the minimum influence on the first modal frequency.